An Assessment of Wound Healing Potential of Argyreia speciosa Leaves - Kuldeep Singh Yadav; Narayan Prasad Yadav; Bindu Rawat; Vineet Kumar Rai; Karuna Shanker; Chandana Venkateswara Rao (The Scientific World Journal)
In North India, poultice of young unfolded leaves of Argyreia speciosa Linn. (Convolvulaceae) is used for healing wounds. In order to find scientific evidence for the traditional utilization of leaves of A. speciosa in wound healing, this investigation was carried out. A linear incision wound of about 3 cm in length and 2 mm in depth and circular excision wound of 177 mm2 full thickness were made on the dorsal region of separate groups (n=5) of anesthetized Swiss albino mice. A simple ointment, developed by including ethanol, ethanol-water, and water extracts (10% each, separately) of A. speciosa, was applied topically to mice once daily for 14 days after wounding. To evaluate the effect of each extract, wound contraction, epithelization period, wound breaking strength, and hydroxyproline content were determined. The water extract of A. speciosa showed accelerated wound healing activity as evidenced by fast wound contraction (96.30±0.52%; P<0.01), rapid epithelization period (11.40±0.60 days; P<0.001), greater wound breaking strength (376.56±21.16 g; P<0.001), and higher hydroxyproline content (16.49±1.12 mg/g; P<0.05) of granulation tissue. The present report supports the traditional use of Argyreia speciosa leaves for wound healing and signify its relevant therapeutic potential.